Dampak Risiko Geopolitik terhadap Respon Kebijakan Moneter di Negara-negara Emerging Market(Pendekatan Panel Dinamis GMM) - Armunanto, Yohanes Novi; Nadya Ramdhani Ikhsana, Nadya; Ayu Nindien, Qurrota Ayu Nindien; Yusuf Afif, Fadeli Yusuf Afif (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the impact of geopolitical risk on monetary policy response in emerging market countries using a dynamic panel approach. The sample includes Indonesia, India, Brazil, Mexico, South Africa, Turkey, the Philippines, and Thailand. Exchange Rate Volatility (ERV) is used as the dependent variable, while Geopolitical Risk (GPR) and Economic Policy Uncertainty (EPU) are the main explanatory variables, with GDP growth as a control variable. To address the dynamic behavior of exchange rates and potential endogeneity, the analysis employs the Generalized Method of Moments (GMM) with the First Difference GMM (FD-GMM) estimator. The results indicate that geopolitical risk and economic policy uncertainty significantly increase exchange rate volatility, while economic growth reduces it. The negative and significant lagged ERV coefficient confirms a mean reversion process, suggesting that monetary authorities respond dynamically to stabilize exchange rates against external pressures. Overall, the findings highlight that exchange rate stability in emerging markets depends on both external risk management and strong domestic economic fundamentals.